2015
DOI: 10.1186/s40623-014-0143-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast and ultrafast Kelvin wave modulations of the equatorial evening F region vertical drift and spread F development

Abstract: In this paper, we investigate the role of eastward and upward propagating fast (FK) and ultrafast Kelvin (UFK) waves in the day-to-day variability of equatorial evening prereversal vertical drift and post sunset generation of spread F/plasma bubble irregularities. Meteor wind data from Cariri and Cachoeira Paulista (Brazil) and medium frequency (MF) radar wind data from Tirunelveli (India) are analyzed together with Thermosphere-Ionosphere-Mesosphere Energetics and Dynamics/Sounding of the Atmosphere using Bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 51 publications
(71 reference statements)
2
30
0
Order By: Relevance
“…Recent research has shown that the vertical plasma drift in the F region above the equator can also be influenced by lower atmospheric variability in the form of tides and planetary waves (e.g., Abdu et al 2006Abdu et al , 2015Maute et al 2014); i.e., forcing from below. Atmospheric gravity waves from the troposphere are also suspected to influence the F-region vertical plasma drift (Li et al 2016) and play a role in the seeding and development of EPBs (e.g., McClure et al 1998;Tsunoda 2010a, b); atmospheric gravity waves therefore represent another form of forcing from below.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that the vertical plasma drift in the F region above the equator can also be influenced by lower atmospheric variability in the form of tides and planetary waves (e.g., Abdu et al 2006Abdu et al , 2015Maute et al 2014); i.e., forcing from below. Atmospheric gravity waves from the troposphere are also suspected to influence the F-region vertical plasma drift (Li et al 2016) and play a role in the seeding and development of EPBs (e.g., McClure et al 1998;Tsunoda 2010a, b); atmospheric gravity waves therefore represent another form of forcing from below.…”
Section: Discussionmentioning
confidence: 99%
“…Planetary wave oscillations in the equatorial ionosphere are more often observed during non-SSW periods, as have been well established from numerous investigations in recent years (see for example, Forbes and Leveroni 1992;Chen 1992;Pancheva et al 2003;Takahashi et al 2009;Abdu et al 2006Abdu et al , 2015a. In their upward propagation, (waves of longer vertical wavelengths attaining higher altitude) these waves nonlinearly interact with ; b The corresponding Digisonde ionograms; c TIMED/GUVI 135.6 nm images extending in the entire longitude span showing the global distribution of the EIA brightness and the patches of brightness depletions indicating plasma bubbles symmetric on either side of the dip equator (Kil et al 2006) tidal modes whereby electric fields are generated in the dynamo region with consequent modulation of the electrodynamical coupling processes.…”
Section: The Variabilities Defining Ionospheric Weathermentioning
confidence: 83%
“…Achieving the desired level of predictive capability on low latitude ionospheric weather disturbances remains to be a long-term objective by the scientific community. Some guidelines can be proposed as examples of those helpful for the continuing progress: (1) Detection and characterization of upward propagating Planetary waves/Kelvin waves at stratospheric and mesospheric heights can be used to predict with a few days in advance their modifications of the EIA, the PRE and the associated ESF/bubble developments, from the knowledge of the upward propagation velocities and other-related characteristics of these waves (Abdu et al 2015a). On a similar principle, the identification of tropospheric convective activity in the equatorial region (associated with the inter-tropical convergence zone, ITCZ) and characterization of the upward propagating gravity waves therefrom will be a step toward predicting ESF/plasma bubble occurrence a few hours ahead of its post-sunset development; (2) Measurement of solar wind and interplanetary magnetic field from satellites (such as the ACE) stationed the at L1 libration point (at 1.5 million km away, and 1 h upstream of the Earth) can be used to predict, with the help of assimilative modeling, the development of equatorial bubble/ESF irregularities and the EIA around 1.5 h ahead of their occurrences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations